Rationally designed insulator-like elements can block enhancer action in vitro - Bondarenko, Vladimir A. (Oxford University Press, 2003)
Insulators are DNA sequences that are likely to be involved in formation of chromatin domains, functional units of gene expression in eukaryotes. Insulators can form domain boundaries and block inappropriate action of regulatory elements (such as transcriptional enhancers) in eukaryotic nuclei. Using an in vitro system supporting enhancer action over a large distance, the enhancer-blocking insulator activity has been recapitulated in a highly purified system. The insulator-like element was constructed using a sequence-specific DNA-binding protein making stable DNA loops (lac repressor). The insulation was entirely dependent on formation of a DNA loop that topologically isolates the enhancer from the promoter. This rationally designed, inducible insulator-like element recapitulates many key properties of eukaryotic insulators observed in vivo. The data suggest novel mechanisms of enhancer and insulator action.